A kind of water-based automobile coating and preparation method thereof

Through the synergistic effect of modified water-based polyurethane resin and talc powder, combined with a variety of additives, a high-density crosslinking network structure and core-shell structure are formed, which solves the wear resistance, weather resistance, corrosion resistance and aging resistance of water-based automotive coatings. The overall performance of the paint has been improved.

CN118256137BActive Publication Date: 2024-12-20广东安捷伦新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410531591.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-29
Publication Date
2024-12-20
Estimated Expiration
2044-04-29

AI Technical Summary

Technical Problem

Existing water-based automotive coatings have shortcomings in wear resistance, weather resistance, corrosion resistance, aging resistance and adhesion, and lack self-repair capabilities.

Method used

Using the synergistic effect of modified aqueous polyurethane resin and modified talc powder, combined with aqueous acrylic resin and curing agent HDI trimer, a high-density crosslinking network structure is formed through the reaction of polyols, diisocyanates, catalysts and chain extenders, and introduced Disulfide bonds, zinc-imidazole coordination bonds and hydrogen bonds are combined with chemical graft modification of silane coupling agents and rare earth metal salts to form a core-shell structure to improve the self-healing and mechanical properties of the coating.

Benefits of technology

It significantly improves the self-repairing performance, wear resistance, weather resistance, aging resistance and mechanical properties of water-based automotive coatings, while enhancing adhesion and hardness, reducing VOC content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a water-based automobile coating and a preparation method thereof, wherein the water-based automobile coating comprises the following raw materials in parts by weight: 45-75 parts of modified water-based polyurethane resin, 20-28 parts of water-based acrylic resin, 3-10 parts of curing agent HDI trimer, 15-20 parts of pigment, 3-5 parts of dispersant, 0.5-1 parts of defoamer, 0.8-1.2 parts of leveling agent, 1-3 parts of anti-settling agent, 0.3-0.8 parts of wetting agent, 4-8 parts of film-forming aid, 12-18 parts of filler, and 20-35 parts of deionized water. The invention uses the synergistic effect of modified water-based polyurethane resin and modified filler to give the water-based automobile coating good self-repairing property, wear resistance, corrosion resistance, weather resistance, aging resistance and other properties, and the water-based automobile coating also has the characteristics of strong adhesion, high hardness, low VOC and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of automobile coatings, and in particular relates to a water-based automobile coating and a preparation method thereof. Background Art

[0002] With the development of industrial economy and urbanization, the automobile industry has also developed rapidly. The rapid development of the automobile industry has a significant pulling effect on the automobile coating market, making automobile coatings the fastest growing coating variety. Since the working environment of automobiles is very harsh and they are exposed to wind and sun all year round, strict requirements are put forward on the performance of automobile coatings. At present, there are two main types of automobile coatings used: solvent-based coatings and water-based coatings. Solvent-based coatings need to be prepared with organic solvents, and a large amount of organic solvents evaporate, which will cause great harm to the workers who spray the coatings, and also pollute the air and cause serious environmental pollution. Therefore, since the 1990s, automobile coatings have begun to shift to water-based automobile coatings.

[0003] Water-based automotive coatings, especially water-based automotive topcoat coatings, are prone to cracking, blistering, shedding, poor waterproofing, etc. when exposed to the scorching sun for a long time. They also have poor weather resistance, poor wear resistance, poor adhesion, low hardness, and slow drying. Moreover, during the use of the car, they are easily damaged by mud, stone splashes, and mechanical abrasions, as well as damage from adhesions, scrapes from branches, and scratches or abrasions from hard objects, which will inevitably cause microcracks and local damage on the surface of the car coating. Due to the limitations of manual repair, if these microcracks and local damage on the surface of the car coating cannot be repaired in time, the mechanical strength of the car coating film will decrease, thereby affecting the service life of the car coating. A Chinese patent with publication number CN105368294A discloses a high-gloss impact-resistant environmentally friendly water-based automotive coating and a preparation method thereof. The water-based coating is prepared by mechanically blending modified water-based polyurethane, nano-amino POSS, polytetrafluoroethylene micropowder wax, deionized water, pigments and fillers, additives, and cross-linking agents in certain weight portions, wherein the modified water-based polyurethane is introduced into the water-based polyurethane by an in-situ modification method using a titanium dioxide precursor and a silicon dioxide precursor, so that the nanoparticles are uniformly arranged and dispersed in the polyurethane emulsion in a directional manner, the coating has good leveling properties, and the nanoparticles have no adverse effects on the appearance of the prepared automotive paint film. The prepared automotive coating film is smooth and bright, has good adhesion, is scratch-resistant, has high gloss, and is excellent in aging resistance and UV resistance. In addition, the invention patent introduces the impact-resistant component amino POSS into the coating, so that the fastness of the paint layer is greatly enhanced, and the water-based coating prepared by the invention has a low VOC content, which meets the environmental protection requirements of automotive coatings. However, the water-based automotive coating prepared by this invention patent has low hardness, poor weather resistance, corrosion resistance and wear resistance, and does not have self-repairing ability. The Chinese patent with publication number CN108070318A discloses a preparation method and application of a self-repairing water-based automotive coating, which fully combines the special physical and chemical properties of nano-silicon dioxide and the advantages of polyurethane to develop a water-based automotive coating with self-repairing function, so that micro-damage to the coating on the surface of the car body, especially the damage that is not easy to detect inside, can be self-repaired by itself without the use of external repair materials, which is of great value. However, the wear resistance, weather resistance, corrosion resistance, aging resistance, adhesion and other properties of the water-based automotive coating in this patent need to be further improved.

[0004] Therefore, developing a water-based automotive coating with excellent hardness, aging resistance, wear resistance, corrosion resistance, weather resistance, adhesion and other properties, and with self-repairing ability is a technical problem that needs to be urgently solved in the current development of automotive water-based coatings. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a water-based automotive coating and a preparation method thereof. The present application utilizes the synergistic effect of modified water-based polyurethane resin and modified talcum powder filler to give the water-based automotive coating good self-repairing performance, wear resistance, corrosion resistance, weather resistance, aging resistance and mechanical properties, and cooperates with water-based acrylic resin and curing agent HDI trimer, under the action of dispersants, defoamers, leveling agents, anti-settling agents, wetting agents, film-forming aids and other auxiliary agents, the self-repairing performance, wear resistance, corrosion resistance, weather resistance, aging resistance and mechanical properties of the water-based automotive coating are further improved, and the water-based automotive coating also has the characteristics of strong adhesion, high hardness, low VOC, etc.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A water-based automobile paint comprises the following raw materials in parts by weight: 45-75 parts of modified water-based polyurethane resin, 20-28 parts of water-based acrylic resin, 3-10 parts of curing agent HDI trimer, 15-20 parts of pigment, 3-5 parts of dispersant, 0.5-1 parts of defoamer, 0.8-1.2 parts of leveling agent, 1-3 parts of anti-settling agent, 0.3-0.8 parts of wetting agent, 4-8 parts of film-forming aid, 12-18 parts of filler and 20-35 parts of deionized water.

[0008] Furthermore, the preparation method of the modified waterborne polyurethane resin specifically comprises the following steps:

[0009] (1) Stir and mix polytetrahydrofuran ether diol, hexamethylene diisocyanate, and catalyst dibutyltin laurate at a speed of 500-600 rpm, heat to 80-100°C and react for 2-3 hours, cool to 50-60°C, add dimethylol propionic acid and 2-hydroxyethyl disulfide and continue to react for 4-5 hours, then slowly drip deionized water, stir and emulsify at a speed of 1000-1400 rpm for 30-45 minutes to obtain a waterborne polyurethane prepolymer containing disulfide bonds;

[0010] (2) Adding Zn to the disulfide bond-containing aqueous polyurethane prepolymer obtained in step (1) 2+ The ethanol solution is adjusted to 45-55°C, and imidazolidinyl urea is added to react for 30-60 minutes to obtain a modified waterborne polyurethane resin.

[0011] Furthermore, the molecular weight of the polytetramethylene ether diol is 1000-1500; the mass ratio of the polytetramethylene ether diol, hexamethylene diisocyanate, catalyst dibutyltin laurate, dihydroxymethylpropionic acid and 2-hydroxyethyl disulfide is (12-18):(10.5-15):(0.02-0.025):1:(1.3-1.6).

[0012] Furthermore, the Zn-containing 2+ The ethanol solution is an ethanol solution of ZnCl2 or Zn(NO3)2·6H2O, wherein the ethanol solution containing Zn 2+ The mass fraction of ZnCl2 or Zn(NO3)2 in the ethanol solution is 12-15%; the molar ratio of ZnCl2 or Zn(NO3)2·6H2O to imidazolidinyl urea is 1:(2-2.5).

[0013] The present invention uses polyol (polytetramethylene ether glycol) and diisocyanate (hexamethylene diisocyanate) to synthesize a waterborne polyurethane prepolymer containing disulfide bonds under the combined action of a catalyst, dibutyltin laurate, and a chain extender, hydroxymethylpropionic acid, and 2-hydroxyethyl disulfide. Then, a Zn-containing prepolymer is added to the waterborne polyurethane prepolymer containing disulfide bonds. 2+ The modified waterborne polyurethane resin is prepared by mixing an ethanol solution and a chain extender, imidazolidinyl urea, to obtain a modified waterborne polyurethane resin; the modified waterborne polyurethane resin has a high-density cross-linked polyurethane interpenetrating network structure as well as disulfide bonds, zinc-imidazole coordination bonds and a large number of hydrogen bonds. When the paint film of an automobile is affected by external scratches, high temperature exposure, humid environment and other factors, it will cause micro scratches, micro cracks and other damages to the paint film of the automobile, causing the main chain of the polyurethane resin to be damaged and broken. When the polyurethane resins at both ends of the damage and break come into contact with each other again, the disulfide bonds in the main chain will undergo bond exchange and recombination, and the broken polyurethane resin will be The molecular chains are reconnected, so that minor scratches and microcracks are weakened or eliminated, completing the self-repair of the paint film; at the same time, hydroxymethyl propionic acid and imidazolidinyl urea are used as chain extenders to introduce multiple hydrogen bonds into the waterborne polyurethane resin. When the paint film of the car is affected by external scratches, high temperature exposure, humid environment and other factors, the hydrogen bonds in the main chain of the polyurethane resin are destroyed, the paint film becomes soft, and the molecular chain segments of the polyurethane resin move, thereby reforming the multiple hydrogen bonds in the polyurethane resin and completing the self-repair of the paint film; and the imidazole group in the chain extender imidazolidinyl urea can react with Zn 2+ Formation of Zn 2+ -imidazole reversible coordination bond, which can break and reorganize, giving the waterborne polyurethane resin good self-healing properties; non-covalent hydrogen bonds, Zn 2+ -The synergistic effect of the imidazole coordination bond and the dynamic covalent bond disulfide bond gives the waterborne polyurethane resin excellent self-healing properties, thereby improving the self-healing properties and weather resistance of waterborne automotive coatings; and the hydrogen bond and Zn 2+ The introduction of imidazole coordination bonds also enhances the mechanical properties of waterborne polyurethane resins; at the same time, the covalent bond network formed by disulfide cross-linking and Zn 2+The non-covalent bond network formed by cross-linking of -imidazole coordination bonds together constitutes a waterborne polyurethane resin with a double cross-linked interpenetrating network structure. The interpenetrating network structure improves the weather resistance and mechanical properties of the waterborne polyurethane resin, thereby further improving the wear resistance, adhesion and weather resistance of the waterborne automotive coating.

[0014] Furthermore, the pigment is any one or more of organic yellow pigment, organic green pigment, organic red pigment, titanium dioxide, and carbon black; the dispersant is any one or more of modified acrylic dispersant, polyether dispersant, or polysiloxane wetting dispersant; the defoamer is any one or two of GPE type polyoxyethylene polyoxypropylene glycerol ether or modified silicone defoamer; the leveling agent is any one or more of water-based fluorine-modified leveling agent, water-based silicone leveling agent, or modified acrylic leveling agent; the anti-settling agent is any one of bentonite and EVA wax; the wetting agent is any one of ethanol, propylene glycol, and glycerol; the film-forming aid is any one of ethylene glycol methyl ether, dipropylene glycol ethyl ether, and propylene glycol ethyl ether acetate.

[0015] Furthermore, the filler is modified talcum powder; and the preparation method of the modified talcum powder specifically comprises the following steps:

[0016] 1) adding talc powder to anhydrous ethanol and ultrasonically dispersing for 30-40 minutes, and then mechanically stirring and mixing at a speed of 1000-1500 rpm for 45-60 minutes to obtain a mixed solution 1, slowly dropping N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane ethanol solution into the mixed solution 1, reacting at 75-85° C. for 4-6 hours, centrifuging, washing, and vacuum drying to obtain talc powder modified with a silane coupling agent;

[0017] 2) Add the talc powder modified with the silane coupling agent obtained in step 1) to the acetic acid solution of chitosan, stir and react for 2.5-4 hours, then add the rare earth metal salt solution thereto, and continue to react for 2-3 hours to obtain modified talc powder.

[0018] Furthermore, the mass ratio of the talc to N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 1:(2.5-3); the mass percentage of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane in the N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane ethanol solution is 20-25%.

[0019] Furthermore, the rare earth metal salt solution is a lanthanum nitrate solution, the mass percentage of the rare earth metal salt in the rare earth metal salt solution is 48-50%; the mass percentage of chitosan in the chitosan acetic acid solution is 2-2.5%; the mass ratio of the talc modified by the silane coupling agent to chitosan and the rare earth metal salt is (0.78-0.8):1:(0.35-0.5).

[0020] In order to facilitate the subsequent grafting modification of talc, the present application first disperses talc in an ethanol solution, and then uses a silane coupling agent N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane to chemically graft the surface of the talc. The talc modified by the silane coupling agent is then electrostatically reacted with chitosan to form a core-shell structure talc with chitosan as the shell and the talc modified by the silane coupling agent as the core. Finally, rare earth metals are used to form coordination bonds with amino groups and hydroxyl groups in chitosan, so that rare earth metal ions are grafted to the shell surface of the talc to obtain rare earth-modified core-shell structure talc; the formation of the core-shell structure improves the hardness, weather resistance and wear resistance of water-based automotive coatings; the modified talc has amino groups, hydroxyl groups and the like that can It combines with modified waterborne polyurethane resin, waterborne acrylic resin and other raw materials to form a dense and stable cross-linked network structure, which improves the compatibility and adhesion between talcum powder filler and other raw materials in waterborne automotive coatings, and further improves the adhesion, weather resistance, wear resistance and corrosion resistance of waterborne automotive coatings. Moreover, rare earth ions can form rare earth metal-amino coordination bonds with amino groups in modified waterborne polyurethane resins, which improves the self-healing properties of waterborne automotive coatings while also improving the compatibility between talcum powder and modified waterborne polyurethane resins. Rare earth compounds have a good absorption effect on ultraviolet rays. The introduction of rare earth elements into talcum powder can improve the aging resistance of talcum powder, thereby improving the aging resistance and weather resistance of waterborne automotive coatings.

[0021] Furthermore, a method for preparing the above-mentioned water-based automotive coating specifically comprises the following steps:

[0022] Step S1, weighing the modified waterborne polyurethane resin, pigment, dispersant, defoamer, and deionized water in order according to the above weight parts, then adding the weighed raw materials into a stirrer, stirring and mixing until the raw materials are uniformly mixed to obtain a mixed material 1, grinding the mixed material 1 with a sand mill to a fineness of ≤3 μm to make slurry A for standby use;

[0023] Step S2, weighing the modified waterborne polyurethane resin, waterborne acrylic resin, defoamer, leveling agent, anti-settling agent, wetting agent, film-forming aid, filler, and deionized water in order according to the above weight proportions, and then adding the above weighed raw materials into a stirrer, stirring and mixing until the raw materials are evenly mixed to obtain intermediate B;

[0024] Step S3, mixing the slurry A obtained in step S1 with the intermediate B obtained in step S2, adding an anti-settling agent and a curing agent HDI trimer, stirring and mixing evenly, and finally adjusting the viscosity with deionized water to obtain a water-based automotive coating.

[0025] Furthermore, in step S1, the stirring speed is 800-1000 rpm, and the stirring time is 45-60 min; in step S2, the stirring speed is 1100-1300 rpm, and the stirring time is 1-2 h.

[0026] Compared with the prior art, the present invention has the following positive and beneficial effects:

[0027] (1) The present invention uses polytetramethylene ether glycol and hexamethylene diisocyanate in the presence of a catalyst, dibutyltin laurate, and chain extenders, hydroxymethyl propionic acid, and 2-hydroxyethyl disulfide, to synthesize a waterborne polyurethane prepolymer containing a disulfide bond, and then adds a Zn-containing prepolymer to the waterborne polyurethane prepolymer containing a disulfide bond. 2+ The ethanol solution and the chain extender imidazolidinyl urea are used to obtain a modified waterborne polyurethane resin having a high-density cross-linked polyurethane interpenetrating network structure and disulfide bonds, zinc-imidazole coordination bonds and a large number of hydrogen bonds; a large number of non-covalent hydrogen bonds, Zn 2+ -The synergistic effect of the imidazole coordination bond and the dynamic covalent bond disulfide bond gives the waterborne polyurethane resin excellent self-healing properties, thereby improving the self-healing properties and weather resistance of waterborne automotive coatings; and a large number of hydrogen bonds and Zn 2+ The introduction of imidazole coordination bonds also enhances the mechanical properties of waterborne polyurethane resins. At the same time, the covalent bond network formed by disulfide cross-linking and Zn 2+ -The non-covalent bond network structure formed by cross-linking of imidazole coordination bonds together constitutes a waterborne polyurethane resin with a double cross-linked interpenetrating network structure. The interpenetrating network structure improves the weather resistance and mechanical properties of the waterborne polyurethane resin, thereby further improving the adhesion and weather resistance of the waterborne automotive coating.

[0028] (2) The present invention uses silane coupling agent N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane to chemically graft the surface of talc powder, and then forms a core-shell structure talc powder with chitosan as the shell and talc powder modified by silane coupling agent as the core through electrostatic action. Finally, rare earth metals are used to form coordination bonds with amino groups and hydroxyl groups in chitosan, so that rare earth metal ions are grafted to the shell surface of talc powder to obtain rare earth modified core-shell structure talc powder; the formation of the core-shell structure improves the hardness, weather resistance and wear resistance of water-based automotive coatings; the modified talc powder also has amino groups, hydroxyl groups and the like that can react with modified water-based polyurethane resins, water-based acrylic resins, etc. The raw materials are combined to form a dense and stable cross-linked network structure, which improves the compatibility and adhesion between talcum powder filler and other raw materials in water-based automotive coatings, and further improves the weather resistance, wear resistance, corrosion resistance and adhesion of water-based automotive coatings; and rare earth ions can form rare earth metal-amino coordination bonds with amino groups in modified water-based polyurethane resins, which improves the self-healing properties of water-based automotive coatings while also improving the compatibility between talcum powder and modified water-based polyurethane resins. Rare earth compounds have a good absorption effect on ultraviolet rays. The introduction of rare earths into talcum powder can improve the anti-aging properties of talcum powder, thereby improving the aging resistance and weather resistance of water-based automotive coatings.

[0029] (3) The present invention modifies the waterborne polyurethane resin and the modified talcum powder. The synergistic effect between the modified waterborne polyurethane resin and the talcum powder gives the waterborne automobile coating good self-repairing performance, wear resistance, corrosion resistance, weather resistance, aging resistance and mechanical properties. In addition, the waterborne polyurethane resin and the curing agent HDI trimer are combined with the dispersant, defoaming agent, leveling agent, anti-settling agent, wetting agent, film-forming agent and other auxiliary agents to further improve the self-repairing performance, wear resistance, corrosion resistance, weather resistance, aging resistance and mechanical properties of the waterborne automobile coating. In addition, the waterborne automobile coating also has the characteristics of strong adhesion, high hardness and low VOC. DETAILED DESCRIPTION

[0030] The following will be combined with the following embodiments in this application to clearly and completely describe the technical solution of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0031] In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All reagents used without special instructions are conventional reagents used in the art, and all reagents or instruments used without specifying the manufacturer are conventional products that can be purchased commercially.

[0032] Example 1

[0033] The preparation method of the modified waterborne polyurethane resin specifically comprises the following steps:

[0034] (1) Stir and mix polytetrahydrofuran ether diol, hexamethylene diisocyanate, and catalyst dibutyltin laurate at a speed of 500-600 rpm, heat to 80-100°C and react for 2-3 hours, cool to 50-60°C, add dimethylolpropionic acid and 2-hydroxyethyl disulfide and continue to react for 4-5 hours, then slowly drop deionized water into the mixture and stir and emulsify at a speed of 1000-1400 rpm for 30-45 minutes to obtain a water-based polyurethane prepolymer containing disulfide bonds; wherein the molecular weight of polytetrahydrofuran ether diol is 1000-1500; the mass ratio of polytetrahydrofuran ether diol, hexamethylene diisocyanate, catalyst dibutyltin laurate, dimethylolpropionic acid and 2-hydroxyethyl disulfide is (12-18):(10.5-15):(0.02-0.025):1:(1.3-1.6);

[0035] (2) Adding Zn to the disulfide bond-containing aqueous polyurethane prepolymer obtained in step (1) 2+ The ethanol solution is adjusted to 45-55°C, imidazolidinyl urea is added and reacted for 30-60 minutes to obtain a modified waterborne polyurethane resin; the Zn-containing 2+ The ethanol solution is an ethanol solution of ZnCl2 or Zn(NO3)2•6H2O, wherein the ethanol solution containing Zn 2+ In ethanol solution of ZnCl2 or Zn(NO 3 ) 2 The mass fraction is 12-15%; the molar ratio of ZnCl2 or Zn(NO3)2·6H2O to imidazolidinyl urea is 1:(2-2.5).

[0036] Example 2

[0037] The preparation method of filler-modified talcum powder specifically comprises the following steps:

[0038] 1) Add talc powder to anhydrous ethanol and disperse it ultrasonically for 30-40 minutes, then mechanically stir and mix at a speed of 1000-1500 rpm for 45-60 minutes to obtain a mixed solution, slowly drop an ethanol solution of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane into the mixed solution, react at 75-85° C. for 4-6 hours, centrifuge, wash, and vacuum dry to obtain talc powder modified with a silane coupling agent; wherein the mass ratio of talc powder to N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 1:(2.5-3); and the mass percentage of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane in the ethanol solution of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 20-25%;

[0039] 2) Add the talc powder modified by the silane coupling agent obtained in step 1) to the acetic acid solution of chitosan, stir and react for 2.5-4 hours, then add the rare earth metal salt solution thereto, continue to react for 2-3 hours, and obtain modified talc powder. The rare earth metal salt solution is a lanthanum nitrate solution, and the mass percentage of the rare earth metal salt in the rare earth metal salt solution is 48-50%; the mass percentage of chitosan in the chitosan acetic acid solution is 2-2.5%; the mass ratio of the talc powder modified by the silane coupling agent to chitosan and the rare earth metal salt is (0.78-0.8):1:(0.35-0.5).

[0040] The modified waterborne polyurethane resin and filler-modified talc used in the following examples and comparative examples are prepared by Examples 1 and 2, respectively, and will not be described in detail in the following examples.

[0041] Example 3

[0042] A water-based automobile paint comprises the following raw materials in parts by weight: 45 parts of modified water-based polyurethane resin, 28 parts of water-based acrylic resin, 3 parts of curing agent HDI trimer, 15 parts of organic yellow pigment, 3 parts of modified acrylic dispersant, 0.5 parts of defoaming agent GPE type polyoxyethylene polyoxypropylene glycerol ether, 0.8 parts of water-based fluorine-modified leveling agent, 1 part of anti-settling agent bentonite, 0.3 parts of wetting agent ethanol, 4 parts of film-forming aid ethylene glycol methyl ether, 12 parts of filler modified talcum powder, and 20 parts of deionized water.

[0043] A method for preparing the above-mentioned water-based automotive coating specifically comprises the following steps:

[0044] Step S1, weighing the modified waterborne polyurethane resin, organic yellow pigment, dispersant, defoamer, and deionized water in order according to the above weight parts, then adding the weighed raw materials into a stirrer, stirring and mixing at a speed of 800 rpm for 60 minutes until the raw materials are evenly mixed to obtain a mixed material 1, grinding the mixed material 1 with a sand mill to a fineness of ≤3 μm to make slurry A for standby use;

[0045] Step S2, weighing the modified waterborne polyurethane resin, waterborne acrylic resin, defoamer, leveling agent, anti-settling agent, wetting agent, film-forming aid, filler, and deionized water in order according to the above weight parts, then adding the above weighed raw materials into a stirrer, stirring and mixing at a speed of 1100 rpm for 2 hours until the raw materials are evenly mixed, to obtain intermediate B;

[0046] Step S3, mixing the slurry A obtained in step S1 with the intermediate B obtained in step S2, adding an anti-settling agent and a curing agent HDI trimer, stirring and mixing evenly, and finally adjusting the viscosity with deionized water to obtain a water-based automotive coating.

[0047] Example 4

[0048] A water-based automobile paint comprises the following raw materials in parts by weight: 60 parts of modified water-based polyurethane resin, 25 parts of water-based acrylic resin, 7 parts of curing agent HDI trimer, 18 parts of pigment titanium dioxide, 4 parts of polyether dispersant, 0.7 parts of modified organic silicon defoamer, 1 part of water-based organic silicon leveling agent, 2 parts of anti-settling agent EVA wax, 0.5 parts of wetting agent glycerin, 6 parts of film-forming aid dipropylene glycol ethyl ether, 16 parts of modified talc powder, and 28 parts of deionized water.

[0049] A method for preparing the above-mentioned water-based automotive coating specifically comprises the following steps:

[0050] Step S1, weighing the modified waterborne polyurethane resin, pigment, dispersant, defoamer, and deionized water in order according to the above weight parts, then adding the weighed raw materials into a stirrer, stirring and mixing at a speed of 900 rpm for 50 minutes until the raw materials are evenly mixed to obtain a mixed material 1, grinding the mixed material 1 with a sand mill to a fineness of ≤3 μm to make slurry A for standby use;

[0051] Step S2, weighing the modified waterborne polyurethane resin, waterborne acrylic resin, defoamer, leveling agent, anti-settling agent, wetting agent, film-forming aid, filler, and deionized water in order according to the above weight parts, then adding the above weighed raw materials into a stirrer, stirring and mixing at a speed of 1200 rpm for 1.5 hours until the raw materials are evenly mixed, to obtain intermediate B;

[0052] Step S3, mixing the slurry A obtained in step S1 with the intermediate B obtained in step S2, adding an anti-settling agent and a curing agent HDI trimer, stirring and mixing evenly, and finally adjusting the viscosity with deionized water to obtain a water-based automotive coating.

[0053] Example 5

[0054] A water-based automobile paint comprises the following raw materials in parts by weight: 75 parts of modified water-based polyurethane resin, 20 parts of water-based acrylic resin, 10 parts of curing agent HDI trimer, 20 parts of pigment carbon black, 5 parts of polysiloxane wetting and dispersing agent, 1 part of defoaming agent GPE type polyoxyethylene polyoxypropylene glycerol ether, 1.2 parts of modified acrylic leveling agent, 3 parts of anti-settling agent bentonite, 0.8 parts of wetting agent propylene glycol, 8 parts of film-forming aid propylene glycol ethyl ether acetate, 18 parts of filler modified talc powder, and 35 parts of deionized water.

[0055] A method for preparing the above-mentioned water-based automotive coating specifically comprises the following steps:

[0056] Step S1, weighing the modified waterborne polyurethane resin, pigment carbon black, dispersant, defoamer, and deionized water in order according to the above weight parts, then adding the weighed raw materials into a stirrer, stirring and mixing at a speed of 1000 rpm for 45 minutes until the raw materials are evenly mixed to obtain a mixed material 1, grinding the mixed material 1 with a sand mill to a fineness of ≤3 μm to make slurry A for standby use;

[0057] Step S2, weighing the modified waterborne polyurethane resin, waterborne acrylic resin, defoamer, leveling agent, anti-settling agent, wetting agent, film-forming aid, filler, and deionized water in order according to the above weight parts, then adding the above weighed raw materials into a stirrer, stirring and mixing at a speed of 1300 rpm for 1 hour until the raw materials are evenly mixed, to obtain intermediate B;

[0058] Step S3, mixing the slurry A obtained in step S1 with the intermediate B obtained in step S2, adding an anti-settling agent and a curing agent HDI trimer, stirring and mixing evenly, and finally adjusting the viscosity with deionized water to obtain a water-based automotive coating.

[0059] Comparative Example 1

[0060] The waterborne automotive coating and its preparation method in this comparative example are the same as those in Example 4, except that the modified waterborne polyurethane resin is replaced by an equal amount of unmodified waterborne polyurethane resin.

[0061] Comparative Example 2

[0062] The water-based automotive coating and its preparation method in this comparative example are the same as those in Example 4, except that the filler-modified talc is replaced with an equal amount of unmodified talc.

[0063] Comparative Example 3

[0064] The water-based automotive coating and its preparation method in this comparative example are the same as those in Example 4, except that the preparation method of the filler-modified talc is different. The preparation method of the modified talc in this comparative example is exactly the same as that in Example 2, except that no rare earth metal salt solution is added in step 2).

[0065] Performance Testing

[0066] The performance of the paint film coatings obtained from the water-based automotive coatings obtained in Examples 3-5 and Comparative Examples 1-3 was tested, and the specific test results are shown in Table 1. The paint film coatings obtained from the water-based automotive coatings obtained in Examples 3-5 and Comparative Examples 1-3 were soaked in 10% HCl and 10% NaOH by mass to test the acid and alkali resistance; the paint film coatings obtained from the water-based automotive coatings obtained in Examples 3-5 and Comparative Examples 1-3 were placed in a neutral salt spray chamber for salt spray resistance test to determine their corrosion resistance; the paint film coatings obtained from the water-based automotive coatings obtained in Examples 3-5 and Comparative Examples 1-3 were placed in an ultraviolet wavelength of 315 nm and an irradiance of 0.54 W / m 2 Place it in a UV aging box for 36 hours to observe whether bubbling or shedding occurs to determine its anti-aging ability.

[0067] Table 1 Performance test results of the paint film coatings prepared from the water-based automotive coatings obtained in Examples 3-5 and Comparative Examples 1-3

[0068]

[0069] It can be seen from the data in Table 1 that the performance of the water-based automotive paint film coating in Examples 3-5 of the present application is better than that of Comparative Examples 1-3, which shows that the synergistic effect between the modified water-based polyurethane resin and talcum powder in the present application improves the good self-repairing performance, wear resistance, corrosion resistance, weather resistance, aging resistance and impact resistance of the water-based automotive coating, and also gives the water-based automotive coating stronger adhesion, higher hardness, lower VOC and other characteristics.

[0070] Comparison of Comparative Example 1 with Example 5 shows that the modified waterborne polyurethane resin has a high-density cross-linked polyurethane interpenetrating network structure as well as disulfide bonds, zinc-imidazole coordination bonds and a large number of hydrogen bonds; a large number of non-covalent hydrogen bonds, Zn 2+ -The synergistic effect of imidazole coordination bond and dynamic covalent disulfide bond improves the self-healing performance, weather resistance and corrosion resistance of water-based automotive coatings; and a large number of hydrogen bonds and Zn 2+ The introduction of imidazole coordination bonds also enhances the impact resistance of waterborne polyurethane resin. At the same time, the covalent bond network formed by disulfide cross-linking and Zn 2+-The non-covalent bond network structure formed by the cross-linking of the imidazole coordination bond together constitutes a waterborne polyurethane resin with a double cross-linked interpenetrating network structure, and the interpenetrating network structure further improves the hardness, adhesion, aging resistance and weather resistance of the waterborne automotive coating. It can be seen from Comparative Example 2 compared with Example 5 that the modified talcum powder of the present application has a core-shell structure, and the formation of the core-shell structure improves the hardness, weather resistance and wear resistance of the waterborne automotive coating. At the same time, the modified talcum powder also has amino, hydroxyl and other groups that can be combined with modified waterborne polyurethane resins, waterborne acrylic resins and other raw materials to form a dense and stable cross-linked network structure, which improves the compatibility and bonding between the talcum powder filler and other raw materials in the waterborne automotive coating, and further improves the weather resistance, wear resistance, corrosion resistance and adhesion of the waterborne automotive coating. It can be seen from the comparison between Comparative Example 3 and Example 5 that the rare earth ions introduced into the modified talcum powder can form rare earth metal-amino coordination bonds with the amino groups in the modified waterborne polyurethane resin, which improves the self-healing performance of the waterborne automotive coating while also improving the compatibility between the talcum powder and the modified waterborne polyurethane resin. In addition, the rare earth compound has a good absorption effect on ultraviolet rays, further improving the aging resistance and weather resistance of the waterborne automotive coating.

[0071] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0072] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A water-based automotive coating, It is characterized in that The water-based automotive coating comprises the following raw materials in parts by weight: 45-75 parts of modified water-based polyurethane resin, 20-28 parts of water-based acrylic resin, 3-10 parts of curing agent HDI trimer, 15-20 parts of pigment, 3-5 parts of dispersant, 0.5-1 parts of defoamer, 0.8-1.2 parts of leveling agent, 1-3 parts of anti-settling agent, 0.3-0.8 parts of wetting agent, 4-8 parts of film-forming aid, 12-18 parts of filler, and 20-35 parts of deionized water; The preparation method of the modified waterborne polyurethane resin specifically comprises the following steps: (1) Stir and mix polytetrahydrofuran ether diol, hexamethylene diisocyanate, and catalyst dibutyltin laurate at a speed of 500-600 rpm, heat to 80-100°C and react for 2-3 hours, cool to 50-60°C, add dimethylol propionic acid and 2-hydroxyethyl disulfide and continue to react for 4-5 hours, then slowly drip deionized water, stir and emulsify at a speed of 1000-1400 rpm for 30-45 minutes to obtain a waterborne polyurethane prepolymer containing disulfide bonds; (2) Adding Zn to the disulfide bond-containing aqueous polyurethane prepolymer obtained in step (1) 2+ ethanol solution, adjusting the temperature to 45-55°C, adding imidazolidinyl urea and reacting for 30-60 minutes to obtain a modified waterborne polyurethane resin; The molecular weight of the polytetramethylene ether diol in step (1) is 1000-1500; the mass ratio of the polytetramethylene ether diol, hexamethylene diisocyanate, catalyst dibutyltin laurate, dihydroxymethylpropionic acid and 2-hydroxyethyl disulfide is (12-18):(10.5-15):(0.02-0.025):1:(1.3-1.6); The step (2) contains Zn 2+ The ethanol solution of ZnCl 2 or Zn(NO 3 ) 2 •6H 2 O ethanol solution, the Zn 2+ ZnCl in ethanol solution 2 or Zn(NO 3 ) 2 The mass fraction of ZnCl is 12-15%; 2 or Zn(NO 3 ) 2 6H 2 The molar ratio of O to imidazolidinyl urea is 1:(2-2.5); The filler is modified talcum powder; the preparation method of the modified talcum powder specifically comprises the following steps: 1) Add talc powder to anhydrous ethanol and disperse it ultrasonically for 30-40 minutes, then mechanically stir and mix at a speed of 1000-1500 rpm for 45-60 minutes to obtain a mixed solution, slowly dropwise add an ethanol solution of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane to the mixed solution, react at 75-85° C. for 4-6 hours, centrifuge, wash, and vacuum dry to obtain talc powder modified with a silane coupling agent; 2) adding the talc powder modified with the silane coupling agent obtained in step 1) to the acetic acid solution of chitosan, stirring and reacting for 2.5-4 hours, and then adding the rare earth metal salt solution thereto, and continuing the reaction for 2-3 hours to obtain modified talc powder; The mass ratio of talc to N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane in step 1) is 1:(2.5-3); the mass percentage of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane in the N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane ethanol solution is 20-25%; In the step 2), the rare earth metal salt solution is a lanthanum nitrate solution, the mass percentage of the rare earth metal salt in the rare earth metal salt solution is 48-50%; the mass percentage of chitosan in the chitosan acetic acid solution is 2-2.5%; the mass ratio of the talc modified by the silane coupling agent to chitosan and the rare earth metal salt is (0.78-0.8):1:(0.35-0.5).

2. A water-based automotive coating according to claim 1, It is characterized in that The pigment is any one or more of organic yellow pigment, organic green pigment, organic red pigment, titanium dioxide, and carbon black; the dispersant is any one or more of modified acrylic dispersant, polyether dispersant, or polysiloxane wetting dispersant; the defoamer is any one or two of GPE type polyoxyethylene polyoxypropylene glycerol ether or modified silicone defoamer; the leveling agent is any one or more of water-based fluorine-modified leveling agent, water-based silicone leveling agent, or modified acrylic leveling agent; the anti-settling agent is any one of bentonite and EVA wax; the wetting agent is any one of ethanol, propylene glycol, and glycerol; the film-forming aid is any one of ethylene glycol methyl ether, dipropylene glycol ethyl ether, and propylene glycol ethyl ether acetate.